EFFECT OF DIFFERENT REGIME OF WTERING ON MILK YIELD AND MILK CONSTITUENTS IN LACTATIANG MURRAH BUFFALOES (Indian Journal of Animal Production and Management, 2016)
Seventy to ninety percent of the total water consumed by the lactating cow is drinking water. Approximately  26 to 34 percent of total water intake is used in milk secretion. In India, generally watering of the animal  is done after milking in the morning and before milking in the evening and rest of the time animal remains  without drinking water which adversely affect in milk production. Therefore, present study was undertaken  to find out the effect of different regime, of watering were studied on milk yield and milk constituents in  lactating Murrah buffalos. The animals were subjected to four regime of watering, adlib (Group I), before  milking (Group II), after milking (Group III) and before and after milking (Group IV). Results revealed that,  the average daily milk yield was highest in group II (8.96 liter) and differed significantly (P
Keywords: Buffalo; Milk composition; Milk yield; Water intake